The Impact of Environmental Factors on Tourism Development on the Barrier Coasts of Poland - Gerstmannowa, Elżbieta (Turyzm/Tourism, 2004)
This paper discusses some problems of tourism-oriented land use on the barrier coasts of Poland. It describes its environmental attributes (land- forms, drift deposits, hydrology, soils, vegetation) as factors exerting an influence on land use and tourism- oriented management. An examination of anthropogenic pressure is followed by a discussion of measures needed to curb and control spreading urbanisation. In conclusion the author has formulated some general guidelines for the protection of these coasts and their utilisation for tourism.